2021
DOI: 10.1098/rsos.201273
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing snake identification with online communities of professional herpetologists and avocational snake enthusiasts

Abstract: Species identification can be challenging for biologists, healthcare practitioners and members of the general public. Snakes are no exception, and the potential medical consequences of venomous snake misidentification can be significant. Here, we collected data on identification of 100 snake species by building a week-long online citizen science challenge which attracted more than 1000 participants from around the world. We show that a large community including both professional herpetologists and skilled avoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…When we asked human experts to identify the same images, they performed slightly better overall (species-level F1 0.76 for 45 classes, F1 0.79 for 27 classes; Table 1), with significant variation among species (Durso et al, 2021). Humans correctly labeled the 248 images in TD3 at the species level 53% of the time (N 26,672), although this varied by species from 83% for Agkistrodon contortrix to 30% for Nerodia erythrogaster.…”
Section: Third Test Dataset (Td3)mentioning
confidence: 97%
See 4 more Smart Citations
“…When we asked human experts to identify the same images, they performed slightly better overall (species-level F1 0.76 for 45 classes, F1 0.79 for 27 classes; Table 1), with significant variation among species (Durso et al, 2021). Humans correctly labeled the 248 images in TD3 at the species level 53% of the time (N 26,672), although this varied by species from 83% for Agkistrodon contortrix to 30% for Nerodia erythrogaster.…”
Section: Third Test Dataset (Td3)mentioning
confidence: 97%
“…For the iNaturalist data, only "research grade" observations, which require a community-supported and agreed-upon identification at the species taxonomic rank, were used. Additionally, we selected a subset (N 336) of these images for additional label validation by human experts (Durso et al, 2021) and found that just five (1.5%) were misidentified (these have been corrected on iNaturalist). HerpMapper is used primarily by experienced enthusiasts with a lot of experience in snake identification; we found no misidentifications in the subset (N 200) we examined.…”
Section: Classes and Training Datasetmentioning
confidence: 99%
See 3 more Smart Citations